PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN LITERASI DIGITAL SISWA SEBAGAI KECAKAPAN ABAD 21 - Ahmad Muflihin; Toha Makhshun (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
The purpose of this study is to analyze the amount of Islamic Education (PAI) teachers' efforts and roles, as well as how they should be involved in developing students' digital literacy. This is due to pupils' inadequate digital literacy, which manifests itself as an inability to process information gained via technology, information, and communication devices. In fact, digital literacy is one of the literacy foundations that are included in 21st-century skills. According to data issued by the Ministry of Communication and Information, Indonesia ranks second in cybercrime and the frequency of false information (hoax), making PAI teachers responsible for increasing digital literacy for students on both a moral and professional level. Interviews with various PAI teachers in Semarang are used in this study. The purpose of the interview was to evaluate how far PAI teachers had progressed in enhancing pupils' digital literacy. According to the findings of this study, PAI teachers' efforts are still minimal. The development of information technology as a method and a learning medium has not been optimized. As a result, enhancing digital literacy requires mutual awareness. Keywords: Islamic Education Teacher, Digital Literacy, 21st Century Skills